MISTAKES WITHIN THE DESCRIPTIVE TEXTS PRODUCED BY UNDERGRADUATE STUDENTS (English Education Journal, 2014)
Learning a target language is actually a process of trial and error, whether as the first, the second or even foreign language. This study is aimed to find out the mistakes within the descriptive texts. The method used in this study was a qualitative approach, and the design was discourse analysis. The data were taken from the 27 descriptive texts written by the fourth semester students of English Department, while the technique of analysis was based on the error analysis theory, involved: collection of a sample, identification, description and explanation. The generic structure result showed that the students could write well in the identification and aspect part, but not in conclusion part. In case of lexicogrammatical features, the use of verbs caused the most number of mistakes, or 132 mistakes (30.07%), while the fewest ones was the use of adjective, found only 4 times (0.91%) of the total mistakes. Generally, the students used the lexicogrammatical features in their writing, even though still need to be improved. The causes of students’ mistakes were mostly due to the interlingual aspect.